Agonism for the bile acid receptor GPBAR1 reverses liver and vascular damage in a mouse model of steatohepatitis. Issue 2 (10th October 2018) - Carino, Adriana; Marchianò, Silvia; Biagioli, Michele; Bucci, Mariarosaria; Vellecco, Valentina; Brancaleone, Vincenzo; Fiorucci, Chiara; Zampella, Angela; Monti, Maria Chiara; Distrutti, Eleonora; Fiorucci, Stefano
ABSTRACT: Nonalcoholic steatohepatitis (NASH) is associated with an increased risk of developing cardiovascular complications and mortality, suggesting that treatment of NASH might benefit from combined approaches that target the liver and the cardiovascular components of NASH. Using genetic and pharmacologic approaches, we show that G protein–coupled bile acid–activated receptor 1 (GPBAR1) agonism reverses liver and vascular damage in mouse models of NASH. NASH is associated with accelerated vascular inflammation representing an independent risk factor for development of cardiovascular diseases and cardiovascular‐related mortality. GPBAR1, also known as TGR5, is a G protein–coupled receptor for secondary bile acids that reduces inflammation and promotes energy expenditure. Using genetic and pharmacologic approaches, we investigated whether GPBAR1 agonism by 6β‐ethyl‐3α, 7β‐dihydroxy‐5β‐cholan‐24‐ol (BAR501) reverses liver and vascular damage induced by exposure to a diet enriched in fat and fructose (HFD‐F). Treating HFD‐F mice with BAR501 reversed liver injury and promoted the browning of white adipose tissue in a Gpbar1‐dependent manner. Feeding HFD‐F resulted in vascular damage, as shown by the increased aorta intima‐media thickness and increased expression of inflammatory genes (IL‐6, TNF‐α, iNOS, and F4/80) and adhesion molecules (VCAM, intercellular adhesion molecule‐1, and endothelial selectin) in the aorta, while reducing the expression of genes involved in NO and hydrogen sulfide generation, severely altering vasomotor activities of aortic rings in an ex vivo assay. BAR501 reversed this pattern in a Gpbar1‐dependent manner, highlighting a potential role for GPBAR1 agonism in treating the liver and vascular component of NASH.—Carino, A., Marchianò, S., Biagioli, M., Bucci, M., Vellecco, V., Brancaleone, V., Fiorucci, C., Zampella, A., Monti, M. C., Distrutti, E., Fiorucci, S. Agonism for the bile acid receptor GPBAR1 reverses liver and vascular damage in a mouse model of steatohepatitis. FASEB J. 33, 2809–2822 (2019). www.fasebj.org